Evaluating Pepper Marketing Distribution using The Structure-Conduct-Performance (SCP) Framework : a Case Study From Kedarpan Village, Kejobong District, Purbalingga Regency - Puspita, Diah Dwi; Fathurrohman, Yusuf Enril; Dumasari, Dumasari (Economics and Business International Conference Proceeding, 2024)
Pepper is a crucial plantation crop with a significant roles in export marketing activities. Pepper marketing activities play a vital role in ensuring pepper reach consumers efficiently. This research aims to profile pepper farmers in Kedarpan Village, analyze market structure, conduct, and performance, and examine the distribution channels of pepper marketing. The study employs qualitative and quantitative descriptive analysis methods using both primary and secondary data. A census method was used to sample all 34 active pepper farmers and 14 traders in Kedarpan Village. The research reveals that the pepper distribution channels in Kedarpan Village consist of 5 channels: Channel 1: Farmer to consumer, Channel 2: Farmer to retailer to consumer, Channel 3: Farmer to collector to retailer to consumer, Channel 4: Farmer to wholesaler, and Channel 5: Farmer to collector to wholesaler for PT JAVA AGRITECH. The largest market share is held by Mr. A at 36%. The CR4 value is 78%, indicating an oligopoly market category. The calculation of HHI yields a result of 2,177, also indicating an oligopoly market category. The lowest marketing margin is found in Channel 4 at Rp 5,000/kg. The highest farmer share is observed in Channel 1 at 100%.